Anthropometric Parameters for Access to Sella Turcica Through the Nostril. Issue 6 (September 2016) - Mohamadi, Yousef; Mousavi, Mahboubeh; Pakzad, Reza; Hassanzadeh, Gholamreza
Abstract : Abstract: The pituitary gland is located in the sella turcica. Pituitary tumors constitute approximately 15% of intracranial benign tumors. "Endo nasal endoscopic trans-sphenoidal" method is an appropriate surgical technique to remove this tumor. In this operation an endoscope enters the nasal cavity through the nostril to reach the floor of the sella turcica. The aim of this study was an anthropometric evaluation of the route of endoscope in this surgery. Two hundred twenty-seven patients (116 women, 111 men) were divided into ≥30, 31 to 61, and ≥61-year age groups. Lateral scanograms of skull were used to measure 3 linear distances and 1 angle. While the mean of the linear variables was significantly higher in men ( P <0.001), this difference was not significant in angular measurement between sexes. More detail evaluation of the age groups showed age- and sex-specific differences in measurements. The authors concluded that it needs to consider the anthropometrical indexes in pituitary surgery.